Influence of different materials of electric vehicle body on low frequency electromagnetic exposure for driver. Issue 1 (February 2021) - Dong, X W; Lu, M
Abstract: For electric vehicles(EVs), in addition to the power system is its core technology, the use of the new body materials with stronger hardness, lighter weight and better shielding performance is also one of the important issues concerned by the EVs industry. The distribution of induction field in the trunk and the central nervous system (CNS) of the driver's is studied with the vehicle body materials are aluminum alloy, non-magnetic steel, metal X and permalloy. The results show that the maximum values of induced electric field intensity(E-field) and induced current density(J-field) in the driver's trunk only reach 2.27% and 67% of the International Commission on Non-Ionizing Radiation Protection(ICNIRP) limits respectively, and the maximum values of E-field and J-field in the driver's CNS only reach 0.29% and 0.62% of the ICNIRP limits respectively. So, the electromagnetic exposure levels of the driver's body are within the safe range in this situation. In short, the EVs body material with the higher resistivity and relative permeability would make the electromagnetic exposure level for the driver's body in a much lower level, and it is also much safer for the driver's body from the perspective of electromagnetic dosimetry.